Impulsivity and quality of life in patients with substance use disorder - Yeşiloğlu, Caner; Tamam, Lut; Demirkol, Mehmet Emin; Yılmaz, Hamdi (Journal of Dependence, 2024)
Objective: This study examines the impact of impulsivity on quality of life among individuals with Substance Use Disorder (SUD). Method: The research was conducted on 45 substance users and 43 voluntary participants who applied to the Training and Research Hospital in Kırşehir between September and October 2023. The participants included 63 men and 25 women, with ages ranging from 18 to 67. The Barratt Impulsiveness Scale (BIS-11) and WHO Quality of Life Scale (WHOQOL-BREF) were used as measurement tools. Results: The findings indicate that individuals with SUD have higher impulsivity and lower quality of life compared to the control group. Specifically, the strongest impact of impulsivity on quality of life was identified in the sub-dimensions of social relationships and psychological health. Conclusion: High impulsivity negatively affects the quality of life of individuals diagnosed with SUD. This study supports the view that intervening in the levels of impulsivity in individuals diagnosed with SUD can improve the quality of life and enhance treatment compliance.